Unraveling the role of local ablative therapies for patients with metastatic soft tissue sarcoma – A retrospective multicenter study of the Bavarian university hospitals - Burkhard-Meier, Anton; Grube, Matthias; Jurinovic, Vindi; Agaimy, Abbas; Albertsmeier, Markus; Berclaz, Luc M.; Di Gioia, Dorit; Dürr, Hans Roland; von Eisenhart-Rothe, Rüdiger; Eze, Chukwuka; Fechner, Katja; Fey, Emma; et al. (Ejso, 2024)
Background: Local ablative therapies (LAT) are increasingly used in patients with metastatic soft tissue sarcoma (STS), yet evidence-based standards are lacking. This study aimed to assess the impact of LAT on survival of metastatic STS patients and to identify prognostic factors. Methods: In this retrospective multicenter study, 246 STS patients with metastatic disease who underwent LAT on tumor board recommendation between 2017 and 2021 were analyzed. A mixed effects model was applied to evaluate multiple survival events per patient. Results: Median overall survival (OS) after first metastasis was 5.4 years with 1-, 2- and 5-year survival rates of 93.7, 81.7, and 53.1 %, respectively. A treatment-free interval ≥12 months and treatment of liver metastases were positively correlated with progression-free survival (PFS) after LAT (HR = 0.61, p = 0.00032 and HR = 0.52, p = 0.0081, respectively). A treatment-free interval ≥12 months and treatment of metastatic lesions in a single organ site other than lung and liver were positive prognostic factors for OS after first LAT (HR = 0.50, p = 0.028 and HR = 0.40, p = 0.026, respectively) while rare histotypes and LAT other than surgery and radiotherapy were negatively associated with OS after first LAT (HR = 2.56, p = 0.020 and HR = 3.87, p = 0.025). Additional systemic therapy was independently associated with a PFS benefit in patients ≤60 years with ≥4 metastatic lesions (for max. diameter of treated lesions ≤2 cm: HR = 0.32, p = 0.02 and >2 cm: HR = 0.20, p = 0.0011, respectively). Conclusion: This multicenter study conducted at six German university hospitals underlines the value of LAT in metastatic STS. The exceptionally high survival rates are likely to be associated with patient selection and treatment in specialized sarcoma centers.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Local ablative therapy; Metastasis; Radiotherapy; Soft tissue sarcoma; Surgery; Systemic therapy